Contemporary terrorism and the true believer. (1st September 2016) - Zekulin, Michael; Anderson, T. D.
ABSTRACT: Living in a time of terror, we argue that there needs to be research on what types of people choose to join Islamist terrorist groups. We think that Eric Hoffer's reflections on the 'true believer' are illuminating. His meditations on the poor, the misfit, the selfish, and the bored provide a framework for a typology of potential terror converts. We work through the literature on terrorism movements, ideology, and the 'global jihadist narrative' as a context to situate Hoffer's ideas within terrorism studies. We analyze Canadian case studies of terrorist actors from various backgrounds and origins, and consider the applicability of our approach from three different perspectives on radicalization. Our determination is that there is at least prima facie evidence to conclude that Hoffer's typology can, in some instances, provide a strong lens through which to understand and predict terrorist converts. However, much more research is necessary before this claim can be substantiated.